2018
DOI: 10.1007/s10753-018-0756-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Boric Acid and Borax on Oxidative Stress, Inflammation, ER Stress and Apoptosis in Cisplatin Toxication and Nephrotoxicity Developing as a Result of Toxication

Abstract: The development of treatment protocols that can reduce side effects in chemotherapy applications is extremely important in terms of cancer treatment. In this context, it was aimed to investigate the effects of boric acid and borax on cisplatin toxicity (nephrotoxicity) in rats. In the experimental phase, eight groups were formed from rats. Boric acid and borax were given to the treatment groups with three different doses using gavage. On the fifth day of the study, cisplatin (10 mg/kg) was administered to all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 40 publications
1
27
0
1
Order By: Relevance
“…As in the present study, boron containing (ulexite, colemanite, borax, etc.) agents used in therapy might induce apoptosis that activates caspase 3 and suppressed certain mechanisms (Hazman, Bozkurt, Fidan, Uysal, & Çelik, 2018). Apoptosis suppressing by borax has also been reported in a small number of aquaculture studies investigating the anti-apoptotic effect of borax on toxicity models (Alak et al 2018;2019a;2019b;2019c).…”
Section: Dna Damage Grade and Apoptosis Levelmentioning
confidence: 85%
“…As in the present study, boron containing (ulexite, colemanite, borax, etc.) agents used in therapy might induce apoptosis that activates caspase 3 and suppressed certain mechanisms (Hazman, Bozkurt, Fidan, Uysal, & Çelik, 2018). Apoptosis suppressing by borax has also been reported in a small number of aquaculture studies investigating the anti-apoptotic effect of borax on toxicity models (Alak et al 2018;2019a;2019b;2019c).…”
Section: Dna Damage Grade and Apoptosis Levelmentioning
confidence: 85%
“…Based on previous studies, it seems reasonable to conclude that the process of chemotherapy leads to trigger the activation of transcription factor NF‐κB and inflammatory cytokines (Keleş et al, ). Recently, several studies have reported that the activation of NF‐κB may induce the progression of some pathologic situations (Hazman, Bozkurt, Fidan, Uysal, & Çelik, ; Shrestha, Sorolla, Fromont, Blancafort, & Flematti, ). According to the results of immunohistochemical NF‐κB staining, positive cell densities increased in the (1 → 3)‐β‐D‐glucan and/or Bortezomib‐treated testes of rats compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was also noted in our study that IL-1b and TNF-a levels have increased in the blood serum of the group given cisplatin and these parameters were found to be at reference levels in ureter, bladder and urethra tissues. Although it is not known whether cisplatin has any effects to the proinflammatory IL-1b and TNF-a levels in ureter, bladder and urethra in literature, it has been found that it increases the level of these cytokines in the uterus, ovary and many organ tissues [34,35]. In addition, it was stated that cisplatin elevated IL-1b and TNF-a levels in renal tissue at oxidative stress-forming dose [36].…”
Section: Il-1b and Tnf-a Levels In Bladder Tissuementioning
confidence: 99%
“…In addition, it was stated that cisplatin elevated IL-1b and TNF-a levels in renal tissue at oxidative stress-forming dose [36]. Hazman et al [35] have expressed that the increased level of IL-1b and TNF-a in blood serum with cisplatin is associated with tissue damage. TNF-a and IL-1b are seen in the early stage of inflammation and initiate the release of ROS [37].…”
Section: Il-1b and Tnf-a Levels In Bladder Tissuementioning
confidence: 99%